Dark sky tourism: economic impacts on the Colorado Plateau Economy, USA. Issue 4 (25th September 2019) - Mitchell, David; Gallaway, Terrel
Abstract : Purpose: This paper aims to examine the economic impact from dark-sky tourism in national parks in the USA on the Colorado Plateau. The Colorado Plateau is a region encompassing parts of Arizona, Colorado, New Mexico and Utah that is known for its dark, star-filled night skies. Tourists in national parks are increasingly interested in observing this natural recreational amenity – especially considering that it is an ecological amenity that is quickly disappearing from the planet. Using a 10-year forecast of visitors to the national parks and using standard input-output modeling, it is observed that, for the first time anywhere, the value of dark skies to tourism in this area. The authors find that non-local tourists who value dark skies will spend 5.8bn over the next 10 years in the Colorado Plateau. These tourist expenditures will generate 2.4bn in higher wages and create over 10, 000 additional jobs each year for the region. Furthermore, as dark skies are even more intense natural amenity in the non-summer months, they have the ability to increase visitor counts to national parks year-round and lead to a more efficient use of local community and tourism-related resources throughout the year. Design/methodology/approach: Using a 10-year forecast of visitors to the national parks and using standard input-output modeling, we find that non-local tourists who value dark skies will spend 5.8bn over the next 10 years in the Colorado Plateau. Findings: These tourist expenditures will generate 2.4bn in higher wages and create over 10, 000 additional jobs each year for the region. Furthermore, as dark skies are even more intense natural amenity in the non-summer months, they have the ability to increase visitor counts to national parks year-round and lead to a more efficient use of local community and tourism-related resources throughout the year. Originality/value: To the best of the authors' knowledge, no other study has attempted to value the environmental amenity of dark skies.